White Framing To The Black: The Case of Racism in USA Legals in The Netflix Series When They See Us (2019) - Lusiana Rachmawati; Rosita Ambarwati; Arri Kurniawan (Edulitics (Education, Literature, and Linguistics) Journal, 2024)
Racism is a social problem that widespread in society. The existence of racial or ethnic differences makes some people receive discrimination. The fact that race is still relevant in modern society. One of the popular social issues related to racism occurred in New York, America, namely the Central Park Five case. In this case, five black and latina teenagers were victims of wrongful arrest by American police for the alleged attempted rape and murder of a white American woman. The purpose of this research is to analyze the racism by white people especially police and people in American law against black people and how whites frame black people in society which leads to racism in the When They See Us series based on the Central Park Five case. The writers used popular literature and popular culture by Ida Rochani Adi (2011) and racial profiling theory by Luiza- Maria Filimon (2015). The research method used is qualitative descriptive. As a result, the form of racism in the series is racial profiling. The components of racial profiling occur in the series, there are police stops, police arrests, police questions, and police brutality. In addition, the frame practice by white people is to demonize black people. It also makes the Central Park Five boys known as the perpetrators in the Central Park Five case.